An Observational Study of Intravenous Granisetron Vs Oral Gabapentin in Preventing Postoperative Nausea and Vomiting after Middle Ear Surgery - Malini Mehta; Akshata Thakurdesai; Sujay Thakkar (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background- Postoperative nausea and vomiting (PONV) is one of the most unpleasant complications after middle ear surgery. Several studies have demonstrated use of gabapentin as antiemetic. This study aims at comparison of intravenous granisetron vs oral gabapentin in preventing PONV. Methods - 64 patients of ASA I or II between the ages of 18 and 65 years were divided equally into two groups. Patients in group I received 3mg granisetron iv 2 minutes and patients in group II received 300 mg gabapentin orally 1 hour prior to surgery. Patients were premedicated with inj. glycopyrrolate and inj. midazolam. Anaesthesia was induced, maintained and reversed in usual manner. Haemodynamic changes and number of episodes of nausea and vomiting were recorded upto 24 hours postoperatively. No statistically significant difference was observed in both the groups at 0 and 1 hour in preventing PONV (p<0.05). Next 24 hours postoperatively neither group showed PONV. No significant haemodynamic changes were observed and there were noside effects in either of the groups.Conclusion- There was no statistically significant difference in prevention of PONV in the patients who had either received inj granisetron 3mg i.v. 2 minutes prior to surgery or oral Gabapentin 300mg 1hour prior to surgery after middle ear surgery without any side effects.